Current DPA and ethoxyquin situation and alternatives to superficial scald control in apples and pears - Calvo, Gabriela (2012)
Trabajo presentado al IV International Conference Postharvest Unlimited 2011. Leavenworth, Washington (Estados Unidos), Mayo 2011